2014
DOI: 10.1021/ie5025062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-Amino Phosphonates under a Neat Condition Catalyzed by Multiple-Acidic Ionic Liquids

Abstract: A simple and efficient method for the synthesis of α-amino phosphonates has been accomplished from aromatic aldehydes, diethyl phosphite, and aromatic amines using multiple-acidic ionic liquids catalysts under solvent-free conditions at room temperature, and these compounds were characterized by H–H correlation spectroscopy (COSY).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Because of the unique properties of low vapor pressure, wide liquid range, high thermal stability, excellent dissolution ability, ionic liquids (ILs) have been introduced as linker into the structures of heterogeneous catalysts. To some surprise, the ionic moiety in the catalyst can more or less stabilize the transition state of reaction through electrosteric activitaion, which is benificial to reaction rate as well as reaction chem- and stereo-selectivity. 1,5,7-Triazabicyclo[4.4.0]­dec-5-ene (TBD), a basic guanidine, is widely used as promoter or catalyst in organic synthesis. Combining the advantages of magnetic nanoparticles and ionic liquids and continuation of effort in the development of environmentally benign protocols, we design a novel ionic modified TBD grafted on the MNPs (Scheme ) and its application in the synthesis of N , N -substituted ureas as well as aza-Michael addtion.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique properties of low vapor pressure, wide liquid range, high thermal stability, excellent dissolution ability, ionic liquids (ILs) have been introduced as linker into the structures of heterogeneous catalysts. To some surprise, the ionic moiety in the catalyst can more or less stabilize the transition state of reaction through electrosteric activitaion, which is benificial to reaction rate as well as reaction chem- and stereo-selectivity. 1,5,7-Triazabicyclo[4.4.0]­dec-5-ene (TBD), a basic guanidine, is widely used as promoter or catalyst in organic synthesis. Combining the advantages of magnetic nanoparticles and ionic liquids and continuation of effort in the development of environmentally benign protocols, we design a novel ionic modified TBD grafted on the MNPs (Scheme ) and its application in the synthesis of N , N -substituted ureas as well as aza-Michael addtion.…”
Section: Introductionmentioning
confidence: 99%
“…The model reaction performed as shown in (Scheme 12) employing 5; 10; 15 or 20 mol% of various ionic liquids at room temperature. [62] SFHEA The recyclability test showed that decreased in the yield of product from 91 % (1st round) to 87 % (5th round).…”
Section: Kabachnick-fields Reactions In the Presence Of Catalysts Under Solvent-free Conditionsmentioning
confidence: 99%
“…SO3H- Functionalized Hydroxy‐Ethyl Amine ionic liquids SFHEAX tested as a catalyst for the synthesis of α ‐Aminophosphonates. The model reaction performed as shown in (Scheme 12 ) employing 5,10,15or20mol% of various ionic liquids at room temperature [62] …”
Section: Catalyzed Processes As Green Approachmentioning
confidence: 99%
“…Their biological applications as herbicides, fungicides, enzyme inhibitors, plant growth regulators, antitumor, antibiotics, peptide mimics, antiviral and pharmacological agents are well documented. These enormous applications have encouraged the development of a number of techniques for the synthesis of α‐aminophosphonates . Kabachnik‐Fields reaction is one of the most direct and efficient routes for the synthesis of α‐aminophosphonates.…”
Section: Introductionmentioning
confidence: 99%